Adaptive equalization for DS-CDMA multi-user communication system using Laguerre filters - Somkur, T.; Benjangkaprasert, C. (2008 International Conference on Control, Automation and Systems : 14-17 October 2008, 2008)
In this paper proposes an adaptive equalizer using Laguerre transversal filter and a RLS algorithm for adaptation in DS-CDMA mobile communication systems. The Laguerre structure is compromise between the FIR and IIR structures, since the Laguerre structure is always stable. We also analyze the Bit Error Rate (BER) performance of the proposed equalizer and the conventional equalizer. The simulation results show that the performances of the proposed equalizer are better than the conventional equalizer, such as fast convergence and lower BER than the conventional adaptive equalizer for every E b / N 0 value.